Moderating effect of religiosity on the relationship between social isolation and psychological well-being - Momtaz, Yadollah Abolfathi; Tengku Abdul Hamid, Tengku Aizan; Ibrahim, Rahimah; Yahaya, Nurizan; Chai, Sen Tyng (Routledge, 2011)
It is known that social isolation is negatively associated to psychological well-being. Hence, it is imperative to identify factors that may moderate this association. This study aimed to examine the moderating effect of religiosity on the relationship between social isolation and psychological well-being among a sample of 1415 community-dwelling older Malay Muslims age 60 years and over. The data for this study came from a national survey entitled Patterns of Social Relationship and Psychological Well Being among Older Persons in Peninsular Malaysia, which was conducted using a cross-sectional research design. Three scales namely WHO-5 Well being Index, Revised Intrinsic Extrinsic Religiosity Scale, and Lubben Social Network Scale were utilised to measure psychological well-being, religiosity, and social isolation, respectively. A four-step moderated hierarchical regression analysis using SPSS (version-13) was employed to test moderating effect of religiosity. The results of this study demonstrated that religiosity significantly moderates relationship between social isolation and psychological well-being, after controlling for age, sex, marital status, level of education, employment status, household income, and place of residence. Based on the findings from this study, the possible educational and therapeutic implications are discussed.